THE REGULATORY MODEL OF COMPLIANCE WITH THE EFFICIENCY OF THE ENERGY SECURITY SYSTEM IN THE SPHERE OF APPLICATION OF RENEWABLE ENERGY SOURCES IN UKRAINE - MATIICHUK, Liubomur (Herald of Khmelnytskyi National University. Economic sciences, 2022)
This article outlines that for most countries of the world, the practical application of renewable energy sources is one of the most priority directions for developing the national energy industry. The annual increase in the volume of energy resources from various renewable energy sources was also noted. The forthcoming book on the growth of the specified indicator was also noted. The countries of the world that currently occupy leading positions in the practical implementation of renewable energy sources on national markets are outlined, including the European Union, the United States of America, China, and India. The fact that energy policy formation is implemented based on the complete domination of non-traditional energy sources over the usual and established fossil and destructive forms for humanity is noted. The strengths of renewable energy sources that should be taken into account are outlined, among them: internal energy characteristics of the potential, which by their content are necessary to satisfy the needs of humanity. Experience convincingly proves that the most significant development of alternative and renewable energy sources should be expected in those countries that today are energy-dependent on fossil and traditional fuels, supplying them to other countries while having a significant external debt burden. It is this circumstance that stimulates own extraction of energy resources through the use of RES; renewable energy sources are available and have an unlimited term and reserves of their use; the economic and ecological component of replacing fossil and dangerous, high-cost energy resources with more accessible, safe resources of non-traditional origin; optimization of price policy by limiting the cost of hydrocarbon resources and minimizing unforeseen losses; complete greening of the environment through the use of environmentally friendly technologies and the use of innovative technological means of work. It has been proven that to achieve maximum efficiency from the functioning of the energy security system in the field of renewable energy sources; it is expedient to observe the following four criteria, which necessarily include: decarbonization as one of the ways to get Ukraine out of the energy crisis; development of a new Strategy for the energy sector of Ukraine in the conditions of post-war recovery; the availability of systematic energy security through the introduction of renewable energy sources are programs and sources of financing; the availability of the routine scope of the application of renewable energy sources with the use of state-market instruments for the regulation of renewable energy in Ukraine. The author's model of regulation of compliance with the efficiency of the energy security system in the practical application of renewable energy sources is proposed.
Keywords: regulation; energy efficiency; regulation efficiency; renewable energy sources; energy security system; RES application; SEB